2023
DOI: 10.1039/d2ra06860e
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the relationship between ferroelectric and photovoltaic properties in CsGeI3 for solar energy conversion

Abstract: In addition to its favorable band gap and strong absorption, CsGeI3 exhibits a large shift current bulk photovoltaic effect of up to 40 μA V−2 in the visible region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The spectroscopy limited maximum efficiency (SLME) method is used to calculate the maximum theoretical power conversion efficiency of solar cells. Theoretically, the maximum solar cell efficiency is defined as [22,45,46]…”
Section: Calculation Of Power Conversion Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The spectroscopy limited maximum efficiency (SLME) method is used to calculate the maximum theoretical power conversion efficiency of solar cells. Theoretically, the maximum solar cell efficiency is defined as [22,45,46]…”
Section: Calculation Of Power Conversion Efficiencymentioning
confidence: 99%
“…The emergence of all-inorganic ferroelectric halide perovskite has thus opened a new chapter in ferroelectric research. Previous studies have shown that strain engineering is an effective approach to improving the ferroelectricity of materials [22][23][24]. Many researchers have explored the effect of strain on ferroelectric perovskite.…”
Section: Introductionmentioning
confidence: 99%
“…1 Chelil et al demonstrated that CsGeI 3 exhibits a large shift current bulk photovoltaic effect of up to 40 μA V −2 in the visible region. 20 Yin et al used Keldysh nonequilibrium Green's function (NEGF) formalism to demonstrate the feasibility of spin, ferroelectric, and optical interactions, which are further detected by a photovoltaic effect in La 2/3 Sr 1/3 MnO 3 /BiFeO 3 /Fe 4 N multiferroic tunnel junctions (MFTJs). 21 However, the impact of ferroelectric polarization on the photocurrent in CsGeX 3 remains unclear at present.…”
Section: Introductionmentioning
confidence: 99%